2008
DOI: 10.1159/000113160
|View full text |Cite
|
Sign up to set email alerts
|

Reproducibility and Accuracy of the ICDAS-II for Detection of Occlusal Caries in vitro

Abstract: Aim: The aim of this study was to assess inter- and intra-examiner reproducibility and accuracy in the detection and assessment of occlusal caries in extracted human teeth using a newly developed visual method for caries diagnosis (International Caries Detection and Assessment System, ICDAS-II). Serial sectioning and microscopy were used as the ‘gold standard’. Methods: The occlusal surfaces of 100 teeth were examined by 4 dentists using the ICDAS-II graded scores 0–6. Thereafter the teeth were serially sectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

20
233
3
21

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 247 publications
(289 citation statements)
references
References 35 publications
20
233
3
21
Order By: Relevance
“…The International Caries Detection & Assessment System (ICDAS) 17 is an accessible set of criteria for dentists, researchers and professors and presents acceptable sensitivity and specificity to the detection of occlusal caries 4,5,10,18,19 . According to this system, caries detection on coronal teeth surfaces is a process that comprises two stages.…”
Section: Introductionmentioning
confidence: 99%
“…The International Caries Detection & Assessment System (ICDAS) 17 is an accessible set of criteria for dentists, researchers and professors and presents acceptable sensitivity and specificity to the detection of occlusal caries 4,5,10,18,19 . According to this system, caries detection on coronal teeth surfaces is a process that comprises two stages.…”
Section: Introductionmentioning
confidence: 99%
“…17 Así mismo, Jablonski-Momeni y colaboradores encontraron una reproducibilidad intraexaminador de 0.73 a 0.83. 15 Estos dos estudios fueron realizados in vitro.…”
Section: Discussionunclassified
“…[12][13][14] Adicionalmente, se han realizado varios estudios para evaluar su reproducibilidad inter e intraexaminador. [15][16][17][18] Jablonsski-Momeni y colaboradores (2008) demostraron reproducibilidad y precisión diagnóstica al usar ICDAS II en 100 molares extraídos, en las diferentes etapas del proceso carioso. Los valores Kappa estuvieron entre 0.62 y 0.83 para los examinadores evaluados.…”
unclassified
See 1 more Smart Citation
“…7 Studies have demonstrated good sensitivity, specificity, reproducibility and diagnostic accuracy for this system. [8][9][10] Though the occlusal pit and fissure areas are approachable and accessible for cleansing and examination, the incidence of carious lesion is more in these sites. This can be attributed to the complex invaginated anatomy of the pits and the fissures.…”
Section: Introductionmentioning
confidence: 99%